Waste analysis of fuselage assembly in panelization group of the 117th NC212i aircraft - Pomalia, Frisca; Iftadi, Irwan; Astuti, Rahmaniyah Dwi (Jurnal Sistem dan Manajemen Industri, 2020)
Dirgantara Indonesia (PTDI) is the single source producer of the NC212i Aircraft. Almost every Aircraft is delivered to the customer over the deadline date. The existence of waste is believed to be one of causing the late delivery. Based on observations of the 117th NC212i Aircraft assembly line, which is precisely at the fuselage assembly in the paneling group, six wastes are identified: waiting, transportation, overprocessing, inventory, and motion. Waste of overproduction does not occur because PTDI applies MTO (Make to Order) system. These 6 wastes are then processed using Waste Assessment Model (WAM). The ranking result is: first place is 25% for defects, second place is 23% for waiting, third place is 17% for motion, fourth place is 15% for inventory, fifth place is 13% for transportation, sixth place is 8% for overprocessing, and seventh place is 0% for overproduction. Three critical wastes based Pareto principle can be minimized, so the delay of aircraft delivery can be reduced.